Isolation and characterization of Candida tropicalis from mixed fruit wastes for bio-ethanol production - T, Dharaneesh; TR, Lokeshwaran; V, Kalaivanan; T, Harish Kumar; K, Sharan; A, Nismal Aswin (International Journal of Environment, Agriculture and Biotechnology, 2024)
The bioethanol production from the biomass is gaining popularity now-a-days all over the world. The bio-ethanol is produced by the process of fermentation of starch, sugars of fruit wastes. Bioethanol can be utilized as bio-fuel for the transport purpose, sanitizer production. Compared to any other sources for bio ethanol production, mixed fruit wastes were cheaper. The present study focussed on utilization of the fruit wastes which are discarded from the local fruit shops and fresh juice shops for the bioethanol production. Mixed fruit wastes were collected and used as the raw material for the bioethanol production takes place via., Candida tropicalis. Yeast is the common species for bio-ethanol, alcohol, biofuel, wine and cider fermentation and conversion of biomass into ethanol. The mixed fruit waste can be converted into biofuel which can acts as an alternative source of bio-ethanol.